Literarnozgodovinska in književnokritična refleksija madžarske književnosti po letu 1980 v slovenščini - Štuhec, Miran (Slavia Centralis, 2020)
Literary-historical and Literary-critical Reflection of Hungarian Literature in the Slovene Language After the Year 1980The article considers the problem of the familiarity of the neighbouring literature and traces the literary-historical and the literary-critical writing that introduced Hungarian literature to the Slovene reader. There are three main findings: firstly, the Slovenes have been acquainted with Hungarian literature since the beginning of the 20th Century; secondly, there is less comprehension of it than could be expected, given the proximity of the nations, their connections and the importance of the literature, and thirdly, an increase in "Slovene" interest is noticeable in recent years.
Keywords: Hungarian literature; reception horizon; dispersion of the literary interest; literary competence